Overcoming the therapeutic limitations of EZH2 inhibitors in Burkitt’s lymphoma: a comprehensive study on the combined effects of MS1943 and Ibrutinib - Jeong, Yurim; Kim, Se Been; Yang, Chae-Eun; Yu, Min Seo; Choi, Wan-Su; Jeon, Youngwoo; Lim, Jung-Yeon (Frontiers in Oncology, 2023)
Enhancer of zeste homolog 2 (EZH2) and Bruton’s tyrosine kinase (BTK) are both key factors involved in the development and progression of hematological malignancies. Clinical studies have demonstrated the potential of various EZH2 inhibitors, which target the methyltransferase activity of EZH2, for the treatment of lymphomas. However, despite their ability to effectively reduce the H3K27me3 levels, these inhibitors have shown limited efficacy in blocking the proliferation of lymphoma cells. To overcome this challenge, we employed a hydrophobic tagging approach utilizing MS1943, a selective EZH2 degrader. In this study, we investigated the inhibitory effects of two drugs, the FDA-approved EZH2 inhibitor Tazemetostat, currently undergoing clinical trials, and the novel drug MS1943, on Burkitt’s lymphoma. Furthermore, we assessed the potential synergistic effect of combining these drugs with the BTK inhibitor Ibrutinib. In this study, we evaluated the effects of combination therapy with MS1943 and Ibrutinib on the proliferation of three Burkitt’s lymphoma cell lines, namely RPMI1788, Ramos, and Daudi cells. Our results demonstrated that the combination of MS1943 and Ibrutinib significantly suppressed cell proliferation to a greater extent compared to the combination of Tazemetostat and Ibrutinib. Additionally, we investigated the underlying mechanisms of action and found that the combination therapy of MS1943 and Ibrutinib led to the upregulation of miR29B-mediated p53-upregulated modulator of apoptosis PUMA, BAX, cleaved PARP, and cleaved caspase-3 in Burkitt’s lymphoma cells. These findings highlight the potential of this innovative therapeutic strategy as an alternative to traditional EZH2 inhibitors, offering promising prospects for improving treatment outcomes in Burkitt’s lymphoma.